Multidimensional Mechanisms of Information‐Cocoon Formation in Major Public Emergencies: An Evolutionary Game and User Network Diffusion Approach - Xiaolin Zhang; Xinchun Li; Quanlong Liu (Systems Research and Behavioral Science, 2026)
ABSTRACT Information cocoons during major public emergencies may intensify cognitive bias and social risk by limiting public exposure to diverse viewpoints and authoritative information. To explain how such cocoons form and may be mitigated, this study develops a cross‐scale framework that links a tripartite evolutionary game among users, platforms and the government with a homophily‐enhanced scale‐free user network diffusion model. Using publicly available social media data, this study calibrates a baseline emergency scenario and simulates macro‐level strategic evolution, micro‐level diffusion and macro–micro coupling. The results reveal three main findings. First, macro‐level results show that users' active search orientation gains evolutionary advantage only when the payoff ratio of active search to recommendation dependence exceeds the relevant critical thresholds, whereas platform algorithm adjustment orientation and the government's active governance orientation are more likely to be sustained when their relative payoff advantages remain sufficient under additional implementation costs, potential losses and cross‐actor interference. Second, micro‐level network mechanisms, including information‐preference homophily, opinion leader influence and strategy‐oriented homophilous rewiring, reshape diffusion and contact structure by affecting local homophily and cross‐orientation contact retention. Information cocoons may therefore arise from recommendation dependence or from structural closure after one strategic orientation becomes widely diffused. Third, cross‐scale coupling analysis shows that macro‐level governance conditions are transmitted to user networks through payoff incentives and connection adjustment. Macro‐level payoff differences shape user strategy updating, whereas platform algorithm adjustment and government active governance affect the retention of heterogeneous ties through connection adjustment. Coordinated proactive orientations on the platform and government sides therefore support the diffusion of active search orientation and the retention of cross‐orientation contact. This study clarifies the cross‐scale formation and governance mechanisms of information cocoons during major public emergencies.